FACTORS ASSOCIATED WITH THE USE OF CONTRACEPTIVE METHODS IN ADOLESCENTS 4TH – 5TH OF SECONDARY EDUCATION FROM TWO EDUCATIONAL INSTITUTIONS IN 2022 - Hurtado-Soto, Marjury Stheysi (2024)
Objective. To determine the factors associated with the use of contraceptive methods in adolescents in the 4th and 5th grade of secondary school from two educational institutions in San Martín de Porres in 2022. Methods. Observational, cross-sectional, analytical and quantitative study. The sample size was 244 participants. A data collection sheet with acceptable reliability was used for the collection of the variables proposed for this study. Statistical analysis was performed with the statistical program SPSS version 26.0. For statistical analysis, the chi-square test and the nonparametric Mann-Whitney U test were used. The approved statistical significance value was p<0.05 with 95% confidence intervals. Results. 37.7% of adolescents have already initiated sexual activity, of which 64.1% of adolescents use contraceptive methods. There was a significant association (p<0.05) for the sociocultural factor: having a romantic partner. Of those who consume alcohol, 60.6% do not use contraceptive methods. There was no significant association for the level of knowledge, sociodemographic factors, source of information and type of family. Conclusions. The factor associated with the use of contraceptive methods in adolescents in the 4th and 5th grades of secondary school is have a romantic partner.